1998
DOI: 10.1136/pgmj.74.874.480
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glycated haemoglobin in non-diabetic patients is associated with an increased mortality in myocardial infarction

Abstract: SummaryDiabetes is associated with increased mortality following acute myocardial infarction compared to the general population. Elevated glycated haemoglobin (HbAJ) in diabetic patients is also associated with increased mortality following acute myocardial infarction, while mild elevations in HbAlc are associated with impaired glucose tolerance. The aim of this study was to determine the influence of HbAlc on outcome of acute myocardial infarction in 253 non-diabetic patients, 46 of whom died in one year. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…Higher levels of fasting glucose and insulin and decreased insulin sensitivity themselves are significant risk factors for cardiovascular disease in both diabetic and nondiabetic populations (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Elevated levels of HbA 1c in nondiabetic individuals have been shown to be an independent risk factor for increased mortality after myocardial infarction (32), and HbA 1c was shown to be a continuously related factor for death from cardiovascular disease as well as all other causes in a population of ϳ5,000 men from the European Prospective Investigation into Cancer and Nutrition (33).…”
mentioning
confidence: 99%
“…Higher levels of fasting glucose and insulin and decreased insulin sensitivity themselves are significant risk factors for cardiovascular disease in both diabetic and nondiabetic populations (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Elevated levels of HbA 1c in nondiabetic individuals have been shown to be an independent risk factor for increased mortality after myocardial infarction (32), and HbA 1c was shown to be a continuously related factor for death from cardiovascular disease as well as all other causes in a population of ϳ5,000 men from the European Prospective Investigation into Cancer and Nutrition (33).…”
mentioning
confidence: 99%
“…T he rate of for mation of glycated protein is considered to depend on the ambient concentration of glucose and half life of the protein [9] . However, there is convincing evidence that concentrations of nonenzymatically glycated protein are increased in many non-diabetic pathological states [10][11][12][13] . Elevated concentrations of glycated hemoglobin have been found in myocardial infarction, chronic renal failure, and nephrotic syndrome patients with normal blood glucose concentrations [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is convincing evidence that concentrations of nonenzymatically glycated protein are increased in many non-diabetic pathological states [10][11][12][13] . Elevated concentrations of glycated hemoglobin have been found in myocardial infarction, chronic renal failure, and nephrotic syndrome patients with normal blood glucose concentrations [10][11][12] . Similarly high concentrations of fructosamine are reported in non-diabetic chronic renal failure and rheumatic arthritis patients [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…But evidences in the literature have documented increased glycated protein levels in some nondiabetic pathological states, like iron deficiency anemia. Some authors have also found that on supplementation with iron therapy, there was a significant decrease in the levels of glycated haemoglobin [5]. Evidence has accumulated, which supports the hypothesis that the glycation reaction, apart from the traditional chronic hyperglycaemia ,can be modulated by the iron status of the patient.…”
Section: Introductionmentioning
confidence: 70%